Aplikasi Pupuk Hayati Diperkaya Biosurfaktan Dietanolamida Olein Sawit dengan Interval Waktu yang Berbeda pada Bibit Kakao (Theobroma cacao L.) - Nurmayulis Nurmayulis; Taufan Rifqi Samudra; Fitria Riany Eris; Abdul Hasyim Sodiq (Jurnal Agroekoteknologi, 2023)
The purpose of this research was to analyze the effects of biofertilizer enriched dietanolamide biosurfactan by palm oil at different time intervals on the growth of cacao seeds (Theobroma cacao L.). This research was conducted on the land of the Integrated Agricultural System area, Serang City, Banten Province. From December 2020 to March 2021. This study used a factorial Randomized Block Design. The first factor is the interval of application time, which as three levels : once every seven days, once every fourteen days, and once every twenty-one days. The second factor is the dose of biofertilizers plus DEA biosurfactant with palm olein at four levels : 10 ml / seed + 5% biosurfactant, 10 ml / seed + 10% biosurfactant, 20 ml / seed + 5% biosurfactant, and 20 ml / seed + 10% biosurfactant, Each treatment was repeated three times in order to obtain thirty-six experimental units. The parameters measured were plant height, number of leaves, stem diameter, plant dry weight, and root canopy ratio. The results showed that the treatment time interval of once every fourteen days had an effect on the number of leaves at 4 WAP (Week After Plant). While the treatment of the dosage of biofertilizers plus 20 ml of palm olein DEA biosurfactant / seed affected the parameters of the number of leaves at 4 and 8 WAP, there was an interaction on plant height at 2 and 4 WAP, number of leaves at 4 and 8 WAP, stem diameter at 12 WAP, and dry weight.